2002
DOI: 10.1093/genetics/160.3.1113
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Disequilibrium in Domestic Sheep

Abstract: The last decade has seen a dramatic increase in the number of livestock QTL mapping studies. The next challenge awaiting livestock geneticists is to determine the actual genes responsible for variation of economically important traits. With the advent of high density single nucleotide polymorphism (SNP) maps, it may be possible to fine map genes by exploiting linkage disequilibrium between genes of interest and adjacent markers. However, the extent of linkage disequilibrium (LD) is generally unknown for livest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Simulations (Kruglyak, 1999) and empirical analyses based on human data (Dunning et al, 2000) suggest that linkage disequilibrium (LD) extends only a few kilobases (kb) around common SNPs; however, other studies indicate that this distance can be greater than 100 kb (Abecasisi et al, 2001) or even beyond 1 Mb (Taillon-Miller et al 2000). Nevertheless, it is suggested that due to genetic drift, admixture, selection and smaller effective population sizes, which reduce allelic heterogeneity, livestock demonstrate greater LD than humans, and LD can extend over several hundred base pairs (McRae et al 2002).…”
Section: Analysis Of Gene Polymorphismsmentioning
confidence: 99%
“…Simulations (Kruglyak, 1999) and empirical analyses based on human data (Dunning et al, 2000) suggest that linkage disequilibrium (LD) extends only a few kilobases (kb) around common SNPs; however, other studies indicate that this distance can be greater than 100 kb (Abecasisi et al, 2001) or even beyond 1 Mb (Taillon-Miller et al 2000). Nevertheless, it is suggested that due to genetic drift, admixture, selection and smaller effective population sizes, which reduce allelic heterogeneity, livestock demonstrate greater LD than humans, and LD can extend over several hundred base pairs (McRae et al 2002).…”
Section: Analysis Of Gene Polymorphismsmentioning
confidence: 99%
“…Overall, the 3 types of Hetian sheep can be clearly distinguished and clustered according to geographical distribution. In LD, when the genetic diversity of the population decreases and the linkage between loci increases, the decay rate of LD is the smallest [22] .…”
Section: Population Linkage Genetic Degreementioning
confidence: 99%
“…In recent years, there has been a dramatic increase of interest in utilizing LD to infer the evolutionary history and process of human populations (Reich et al, 2001;Ardlie et al, 2002 ;Dawson et al, 2002 ;Gabriel et al, 2002) and to identify genes for disease or yield traits by association analyses with DNA-based markers (Remington et al, 2001 ;Ardlie et al, 2002). The efficacy of LD analysis in population genetic studies and gene mapping depends on the level of LD in the population studied, its distribution and heterogeneity across the genome, and its relationship with genetic or geographic distances (Farnir et al, 2000 ;McRae et al, 2002 ;Liu et al, 2006). The pattern of LD decay is well known in human populations, where the relationship between the LD and physical distance is graphically elucidated to infer the origin and evolution of humans (Tishkoff et al, 1996(Tishkoff et al, , 2001Tishkoff & Williams, 2002).…”
Section: Introductionmentioning
confidence: 99%